The correlation between physical activity and individuals diagnosed with epilepsy: A literature review (Research, Society and Development, 2025)
Epilepsy is the second most impactful neurological condition in terms of years of life lost, with an approximately sixfold increase in mortality and one-third of patients being refractory to treatment despite recent advances. Physical activity is a promising and safe therapeutic possibility for these patients, as it reduces seizures, and improves quality of life. However, there are still many barriers to this approach, such as fear of increased seizures, lack of time, and insufficient knowledge and training among healthcare professionals. This article aims to conduct a comprehensive literature review of the benefits and risks of this therapeutic approach. This study consists of a literature review based on structured database research and analysis of articles published between 2018 and 2023 in PubMed and Scielo, aiming to explore the benefits and potential risks of physical exercise in individuals with epilepsy. Conclusively, when performed appropriately and under supervision, physical activity offers significant advantages in controlling epileptic seizures, including enhanced quality of life, reduced anxiety symptoms, improved cognitive function, and increased brain plasticity.